Cross‐Cultural Study of Cognitive and Metacognitive Processes During Math Problem Solving. (3rd October 2013) - Cozza, Barbara; Oreshkina, Maria
Abstract : The purpose of this qualitative study was: (a) to explore the cognitive and metacognitive processes of mathematics problem‐solving discourse of 10‐year‐old students in Russia, Spain, Hungary, and the United States; and (b) to explore the patterns of social interactions during small group work. Data were analyzed using a cognitive/metacognitive framework adopted from Artzt and Armour‐Thomas. The analysis of think‐aloud transcripts, students' reflective journals, and field observation notes revealed similar patterns of cognitive/metacognitive processes of the problem‐solving discourse at the four research sites and distinct patterns of social interactions. Implications of how children used metacognition to impact learning during mathematics problem solving are discussed.